Transformasi Kinerja Kontraktor melalui Inovasi Rantai Pasok pada Proyek Pengendalian Banjir dan Pembangunan Embung di Kabupaten Dharmasraya - Sardi, Idris; Carlo, Nasfryzal; Adriadi, Riki (Jurnal Talenta Sipil, 2025)
Infrastructure projects require coordination and high efficiency in implementation. Innovation in supply chain management was identified as one of the key factors to improve contractor performance, which includes time, cost efficiency, and quality of work output. The dam construction project and flood control facilities/infrastructure in Dharmasraya district has recently been seen to be quite active, but nevertheless, the problem of delay in completing work seems to be a coloring in the reports of these projects. This is due to the lack of planning and material management from the implementing contractor. This is quite concrete evidence that there is a problem with the performance of the contractor executing the project. The purpose of this study is to identify the dominant factors and factors that affect the construction supply chain in the Flood Control Facility Development and Infrastructure project in Dharmasraya district, and determine the relationship between the supply chain (factor X) and contractor performance. This study uses a quantitative method by distributing questionnaires to respondents. The selected respondents are parties related to the Batanghari Hilir flood control infrastructure development project in Dharmasraya district for the 2019-2022 fiscal year. The results of this study are found to be 6 factors that affect the construction supply chain in the Embung Development project and flood control facilities/infrastructure in Dharmasraya district. The 6 factors are material factors, procedural factors and price changes, financial factors, process factors and work plans, work implementation factors, and procurement and payment factors. The SCM factor that has the most dominant influence is the material factor. The practical recommendations resulting from this study can be used by contractors and other stakeholders to optimize project performance through effective supply chain innovation.